2011
DOI: 10.1002/jmri.22849
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of skeletal muscle degeneration in patients with myotonic dystrophy type 1 using MRI

Abstract: Purpose: To identify MRI biomarkers that could be used to follow disease progression and therapeutic efficacy in one individual muscle in patients with myotonic dystrophy type 1 (DM1). Materials and Methods:Lower limb MRI and maximal ankle dorsiflexor strength assessment, using a hand-held dynamometer, were performed in 19 DM1 patients and 6 control subjects. The volume of residual muscle tissue of Tibialis Anterior (TA) muscle was chosen as an index for muscle atrophy, and the T2-relaxation-time of the residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 27 publications
4
54
3
2
Order By: Relevance
“…Several studies have demonstrated lower limb muscle involvement in DM1 patients [10][11][12][13]; however, the detailed distribution of upper limb muscle involvement has not been reported previously.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have demonstrated lower limb muscle involvement in DM1 patients [10][11][12][13]; however, the detailed distribution of upper limb muscle involvement has not been reported previously.…”
Section: Discussionmentioning
confidence: 87%
“…Как использовать получаемые биомаркеры с учетом их полезности при выявлении даже минимальных изменений в результате терапев-тического вмешательства на малых выборках больных? Поскольку они не зависят от субъективной оценки состояния и имеют высокую воспроизводимость, боль-шинство количественных МРТ-показателей -лучшие кандидаты для подтверждения эффекта и мониторин-га результатов терапии [67,68]. Данный вывод основан на предположении о том, что терапевтическое веще-ство будет вызывать одинаковую степень изменений при всех возможных методах оценки результатов, что, однако, не соответствует действительности.…”
Section: лекции и обзорыunclassified
“…Quantitative MRI can objectively measure these changes: on T 2 relaxometry muscle T 2 is elevated in myotonic dystrophy [10], Duchenne muscular dystrophy [11], juvenile dermatomyositis [6] and amyotrophic lateral sclerosis [12], while skeletal muscle magnetisation transfer ratio (MTR) is decreased in limb girdle muscular dystrophy [13] and Charcot-Marie-Tooth disease [14]. Muscle fat content has been quantified by T 1 -relaxometry [15], proton spectroscopy ( 1 H-MRS) [1619], T 2 relaxation modelling [2022] and chemical-shift based Dixon fat-water separation [23] providing maps of the proportion of fat to water, or “fat fraction” (FF) [10, 22, 2426].…”
Section: Introductionmentioning
confidence: 99%